Respuesta :
Step-by-step explanation:
You're asking why
[tex] {- 2(x + 3y) = 18} = y = - 3 - \frac{x}{3} [/tex]
let's transpose the first equation for y
-2x-6y=18
-6y=18+2x
6y=-18-2x
y=-18/6-2x/6
y=-3-⅓x as required
For this I would isolate y from the beginning.
Heres how I would solve it:
-2(x + 3y) = 18 --> 18 divided by (-2) is (-9), so (x + 3y) must be equal to (-9)
x + 3y = -9 --> now I would begin to isolate for y:
3y = -9 -x
y = (-9-x) ÷ 3 --> dividing each term by 3 would give me:
y = -3 - x/3 --> x stays the same because it doesn't have a definite answer.
Hope this helps (〃▽〃)